Necklacelike Pattern of Vortex Bound States - Zhiyong Hou; Kailun Chen; Wenshan Hong; Da Wang; Wen Duan; Huan Yang; Shiliang Li; Huiqian Luo; Qiang-Hua Wang; Tao Xiang; Hai-Hu Wen (Physical Review X)
A vortex is a topological defect in the superconducting condensate when a magnetic field is applied to a type-II superconductor, as elucidated by the Ginzburg-Landau theory. Because of the confinement of the quasiparticles by a vortex, it exhibits a circular-shaped pattern of bound states with discrete energy levels, as predicted by the Caroli–de Gennes–Matricon theory in 1964. Here, however, we report a completely new type of vortex pattern which is necklacelike in an iron-based superconductor KCa_{2}Fe_{4}As_{4}F_{2}. Our theoretical analysis shows that this necklacelike vortex pattern arises primarily from selective off-shell interference between vortex bound states of opposite angular momenta in the presence of rotational symmetry breaking due to disorders. This fascinating effect can be observed in a system with a small Fermi energy and wave vector, conditions fortuitously met in our samples. Our results not only disclose a novel vortex structure, but also unravel a completely new quantum phenomenon in the superconducting condensate.